The Political Economy of European Wine Regulations - Giulia Meloni; Johan Swinnen (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2012)
The EU wine market is heavily regulated. Despite the many distortions in the wine market as a consequence, refirming the regulations has proven difficult. This paper analyses the political economy mechanism that created the existing set of wine regulations. We document the historical origins of the regulations and relate these to political pressures that resulted from international integration, technological innovations and economic developments.
Keywords: K23; L51; N44; N54; Q13; 330; European agriculture; wine history; regulation; appellations; institutions